KEEFEKTIFAN PENGGUNAAN MULTIPLE INTELLIGENCES DALAM PROSES PEMBELAJARAN SAINS PADA SISWA SD DI KOTA AMBON - Yuli Filindity; Sukardjo Sukardjo (Program Studi Pendidikan Kimia FKIP Universitas Pattimura, 2011)
This study attempts to investigate how the science learning process applies different multiple intelligences. The problem is focused on the students’ scientific performances and attitudes in science learning. This study was a quantitative descriptive study. The research population comprised all students of SD Negeri Latihan 1 Ambon and the sample was Year III students. The sample was selected using the purposive sampling technique. The data were collected by means of the Multiple Intelligences Test to classify the students into learning centers. Then in the teaching and learning activities, the students were grouped into learning centers for the assessment of their scientific performances and attitudes. The quantitative data were collected and analyzed using the descriptive technique. The results of the study show that the application of multiple intelligences in the science learning process is effective. When the students learn in the learning centers, they are able to perform in accordance with the objectives they have to attain in science learning